Effect Of Brand Image, Promotion and Product Quality on The Customers Decision at Panin Bank - Napitupulu, Duta Natalie; Harahap, Rahmat Alamsyah; Hutabarat, David Samuel; Sitorus, Martin Leonardo; Depari, Kevin Haganta; Hakim, Andy (Lembaga Riset Ilmiah, 2024)
PT. Panin Bank Tbk Medan Branch currently has offices on Jl Pemuda No.16 – 2, Aur Village, Medan Maimun District – Medan North Sumatra Province. The problem of bank brand image is well known among urban communities but is not so well known in suburban areas. The promotional problem is that the results of promotional activities carried out by the bank have not been maximized. The problem with product quality is that it is still far from the product quality offered by several other private banks. The study's nature is explanatory research, and the research methodology is quantitative descriptive research. Interviews, documentation studies, and questionnaires are some of the methods used to collect data. In multiple linear regression, three classical assumptions are tested: multicollinearity, heteroscedasticity, and normalization. The research population served as the analytical approach. There were 200 clients in the study population; 133 were selected by simple random sampling, and 30 completed validity and reliability testing. Customers' decisions are positively impacted by the finding that the simultaneous (f test) effects of brands images, promotion, and product quality F count 517,729 > F table 2.67 with sig. 0.000 < 0.05. Partially (t test) the brand image of t count 0.026 < t table 1.65657 and sig. 0.979 > 0.05, the promotion t count 5,094 > t table 1.65657 and sig. 0,000 < 0.05, the product quality of t count 3.704 < t table 1.65657 and sig. 0.000 < 0.05. With an Adjusted R Square determination coefficient test result of 0.922, it can be concluded that brand image, promotion, and product quality account for 92.2% of customers' decisions, with other variables accounting for the remaining 7.8% of the explanation